Inertia in community planning projects in developing countries: the case of Mukuru Special Planning Area Project, Nairobi, Kenya - Barake, Bosibori (My University, 2021)
The need to solve the challenges of informal settlements in cities and countries resulted in a bold move by the Nairobi County government to declare Mukuru Informal Settlement a Special Planning Area in August 2017. This created an opportunity to plan for the settlement formally within a two-year period. This has extended beyond this period and the planning process is still not finalized. By evaluating aspects of this project, this study sought to understand the factors that have delayed the completion (approval) of the Mukuru Special Planning Area to date since its inception and what may likely have improved the completion of the project. The dynamics of this project are critical in the physical implementation of aspects of the draft plan are already taking place and shape in the settlement even though the plan is yet to be approved by the local authorities responsible. The study used secondary and primary data collection methods through a case study approach. The research found that various challenges have faced the community participatory planning process. The challenges were beyond the control of those facilitating the participatory planning and relate primarily to the wide scope of the project, various interests at play and that political will, financial support and commitment were lacking
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Urban Studies (Urban Management), 2021